Bulgaria's Integration into the Pan-European Economy and Industrial Restructuring - Kaminski, Bartlomiej; Ng, Francis (World Bank, Washington, DC, 2012)
This paper looks at Bulgaria's industrial restructuring through the lenses of its evolving specialization in international division of labor and integration into international markets with a special emphasis on EU markets. Its major findings can be summarized as follows: (1) Developments in Bulgaria's exports, its major drivers and factor content, during the "second transition" following the 1996 crisis have become reminiscent of developments in the early 1990s in European transition economies that have stayed the reform course. (2) The evolution of Bulgaria's total exports in terms of factor intensities before the "second transformational" recession was a testimony to aborted economic reforms. It not only defied expectations derived from the experience of CEEC-10 economies and its production factor endowments but also dramatically increased the cost of adjustment to market conditions for the economy as a whole. (3) Exports of unskilled labor-intensive products continue towering over other exports even during the current expansionary phase. The composition of top performers in EU markets indicates the shift toward natural resource and capital-intensive products. Bulgaria's export offer in EU markets has begun shifting toward more processed goods, mostly products of electro-engineering sectors. Bulgarian producers have made significant strides in information communication technology products and automotive parts. Trade in parts and engineering products has displayed strong growth. The returns usually associated with liberal reforms, that is, gains in competitiveness combined with a shift toward products in line with the country's endowments in production factors began to surface only recently. In contrast to the period preceding the second transformational recession in 1996-97, gains in competitiveness derive from corporate and industrial restructuring and not from subsidies.